2007
DOI: 10.1002/hup.836
|View full text |Cite|
|
Sign up to set email alerts
|

Serotonin reuptake inhibitors in pregnancy and the risk of major malformations: a systematic review

Abstract: The reviewed studies suggest that exposure to fluoxetine, sertraline, citalopram and venlafaxine in early pregnancy is not associated with an increased risk of major congenital malformations. For paroxetine, recent data call for caution in prescribing such a drug in early pregnancy. For the other SRIs, the risk remains substantially undetermined, as data are so far scanty. Given this background, large prospective cohort studies are urgently needed to better assess the risk/benefit ratio of SRIs-treatment durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 55 publications
0
18
0
2
Order By: Relevance
“…Por otra parte, si la depresión es grave o no responde a la psicoterapia sola, se recomienda una combinación entre fármacos y TCC (48,56,57). Al respecto, una reciente revisión de De Rubeis y cols (59) con imagen funcional de resonancia magnéti-ca (fMRI) demuestra que la TCC resulta tener una eficacia similar a aquella de la mayor parte de los fármacos antidepresivos, reduciendo el riesgo de recaída, incluso después de una eventual interrupción de la terapia farmacológica.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por otra parte, si la depresión es grave o no responde a la psicoterapia sola, se recomienda una combinación entre fármacos y TCC (48,56,57). Al respecto, una reciente revisión de De Rubeis y cols (59) con imagen funcional de resonancia magnéti-ca (fMRI) demuestra que la TCC resulta tener una eficacia similar a aquella de la mayor parte de los fármacos antidepresivos, reduciendo el riesgo de recaída, incluso después de una eventual interrupción de la terapia farmacológica.…”
Section: Discussionunclassified
“…Es una experiencia común que muchas mujeres que padecen de DAP no quieran utilizar fármacos a causa del posible riesgo de malformaciones mayores, de complicaciones perinatales, así como de potenciales efectos negativos sobre el desarrollo del niño en el corto o largo plazo (48,49). Así, la Guía Clínica para el tratamiento de personas con depresión (23) señala como contraindicados durante el primer trimestre del embarazo a la paroxetina, las benzodiacepinas, el litio, la carbamazepina y el ácido valproico.…”
Section: Introductionunclassified
“…36 Many studies look at major malformations, which Bellantuono and colleagues 29 define as a malformation needing medical-surgical treatment and induced by fetal exposure to a drug (with potential teratogenic effect) during the first trimester of pregnancy. 29 Earlier studies tended to find no evidence of increased risk for congenital malformations associated with SSRI use in early pregnancy 37 above the existing baseline, but more recent studies and meta-analytic studies of previous research have found some evidence of an association between SSRI use in early pregnancy and congenital malformations. Donnelly and Paton, 38 in a review article, found mixed findings, in prospective, retrospective, and case-controlled studies.…”
Section: Ssri Use In Early Pregnancymentioning
confidence: 95%
“…If depression is not too severe, a less invasive alternative, such as CBT or IPT-A should be considered as a first line treatment. 29,34 However, adolescents may have financial and/or motivational restrictions that will decrease the effectiveness of psychotherapy. 5.…”
Section: Considerations and Recommendations For Treatment Of Depressimentioning
confidence: 99%
See 1 more Smart Citation